Pengembangan Media Pembelajaran Interaktif Berbasis Website Materi Berpikir Komputasional Kelas X SMKN 17 Samarinda - Riendy, Riendy; Prayogo, M. Ari (Jurnal Sistem Informasi, Teknik Informatika dan Teknologi Pendidikan, 2025)
This study aims to develop and evaluate the feasibility of web-based learning media by utilizing WordPress, especially in computational thinking materials for grade X students at SMK Negeri 17 Samarinda. The method used in this study is Research and Development (R&D) by adopting a 4D model, which includes the stages of Define, Design, Development, and Disseminate. The data collection process is carried out through observation, questionnaire distribution, and interviews. The collected data was analyzed quantitatively, then converted into qualitative descriptive data using the Likert scale. The research subjects consisted of one material expert, three media experts, one informatics teacher of SMK Negeri 17 Samarinda, and 74 students of class X at the school. The results of the evaluation showed that the subject matter expert gave an average score of 73, which belongs to the "Worthy" category. Meanwhile, media experts gave an average score of 110.33, included in the "Very Feasible" category, and students gave an average score of 104.31, also included in the "Very Decent" category. Based on the results of the assessment, it can be concluded that the Development of Website-Based Interactive Learning Media for Class X Computational Thinking Materials (Case Study: SMK Negeri 17 Samarinda) was declared "Very Feasible" to be used in the learning process.